Diseño e implementación de un secador de semillas de cacao en la hacienda "La Esmeralda". - Gaibor Velasco, Erick Iván (2017)
The farm 'La Esmeralda', located in the province of Los Ríos, Montalvo Canton has an extension of six hectares wherein there are approximately 8,500 cocoa plants ' CCN-51 ' that produce a total amount of 150hundredweight of moist cocoa per year. Because there is no cocoa seed dryer, the owners sell the product at a price below 65% of the dry seed value. Thereby, the main objective of this research work is to design and implement a cocoa seed dryer to reduce drying time, increase its quality and increase the economic income of the producer. In order to reach this goal, a rotary dryer was designed, constructed and implemented. It is basically formed by a hopper, a drying chamber, the cover, a LPG burner, the dryer support, a lifting system to carry out the discharge of the dry product, a motor reducer and the control system. The results show that the drying process meets the design requirements, reducing the amount of internal cocoa moisture from 60% to 7%, which generates a better quality of the product and economic income to the producer as well. In conclusion, notwithstanding the limitations, the study set out that the machine of cocoa dryer significantly contributed to the dehydration of the seed, that is to say, reduced the drying time, replacing the traditional process by an industrial system.